A text message based weight management intervention for overweight adults. (6th June 2013) - Donaldson, E. L.; Fallows, S.; Morris, M.
Abstract: Background: Weight management interventions can be extended using mobile telephone technology to deliver support in real‐time, real‐world settings. The present study aimed to determine whether text messaging helped patients maintain or lose weight following a weight‐loss programme. Methods: In this controlled study, overweight and obese [body mass index (BMI) >30 kg m –2 or >28 kg m –2 with co‐morbidities] adults who completed a weight‐loss programme participated in an additional 12‐week text message intervention [Lifestyle, Eating and Activity Programme (LEAP) Beep]. Patients were allocated goals for steps, fruit, vegetable and breakfast consumption. Patients regularly 'texted' their progress and received tailored practitioner feedback. Pre/post‐intervention body weight, waist circumference (WC), BMI, quality of life (QOL), anxiety and depression measurements were compared retrospectively with a control group offered weight checks only. Results: Compared to control ( n  =   17), the intervention group's ( n  =   17) body weight, WC and BMI reduced significantly (−1.6 versus 0.7 kg, P  =   0.006; −2.2 versus 1.5 cm, P  =   0.0005; −0.6 versus 0.7 kg m –2, P  =   0.03, respectively). QOL and depression scores also improved (−6.8 versus 1 point, P  =   0.134; −0.2 versus 0.2 points, P  =   0.228). No difference was observed in anxiety scores between the groups. Intervention versus control group follow‐up attendance improved significantly (4.4 versus 1.7 attendances, P  =   0.0005). Conclusions: LEAP Beep promoted losses in weight, WC and BMI, and improved QOL parameters and follow‐up attendance. Text messaging is a cheap, portable, convenient and innovative medium facilitating goal setting, self‐monitoring and information exchange. Further improvements to automation at the same time as maintaining individual support are necessary to ease practitioner burden. Text messaging offers cost‐efficient dietetic input, opening up possibilities for practitioner‐to‐patient support and yields positive weight outcomes following initial weight loss.